Risk of COVID 19 in patients with inflammatory bowel diseases compared to a control population. Issue 3 (March 2021) - Maconi, Giovanni; Bosetti, Cristina; De Monti, Alberta; Boyapati, Ray Kiran; Shelton, Edward; Piazza, Nicole; Carvalhas Gabrielli, Anna Maria; Lenti, Marco Vincenzo; Bezzio, Cristina; Ricci, Chiara; Greco, Salvatore; Romeo, Samanta; et al.
Abstract: Background: It is unclear whether patients with inflammatory bowel disease (IBD) are at increased risk of COVID-19. Objectives: This observational study compared the prevalence of COVID-19 symptoms, diagnosis and hospitalization in IBD patients with a control population with non-inflammatory bowel disorders. Methods: This multicentre study, included 2733 outpatients (1397 IBD patients and 1336 controls), from eight major gastrointestinal centres in Lombardy, Italy. Patients were invited to complete a web-based questionnaire regarding demographic, historical and clinical features over the previous 6 weeks. The prevalence of COVID-19 symptoms, diagnosis and hospitalization for COVID-19 was assessed. Results: 1810 patients (64%) responded to the questionnaire (941 IBD patients and 869 controls). IBD patients were significantly younger and of male sex than controls. NSAID use and smoking were more frequent in controls. IBD patients were more likely treated with vitamin-D and vaccinated for influenza. Highly probable COVID-19 on the basis of symptoms and signs was less frequent in the IBD group (3.8% vs 6.3%; OR:0.45, 95%CI:0.28–0.75). IBD patients had a lower rate of nasopharyngeal swab-PCR confirmed diagnosis (0.2% vs 1.2%; OR:0.14, 95%CI:0.03–0.67). There was no difference in hospitalization between the groups (0.1% vs 0.6%; OR:0.14, 95%CI:0.02–1.17). Conclusion: IBD patients do not have an increased risk of COVID-19 specific symptoms or more severe disease compared with a control group of gastroenterology patients.